THE LITHUANIAN EQUITY MARKETIN 1993–2008: REASONS FOR ITS DECLINE - Paškevičius, Arvydas; Dubinskas, Petras (Ekonomika, 2009)
This paper is an attempt to investigate the causes of the recurrent decline in the equity market in the period of the last fifteen years in Lithuania. Empirical methods are used to establish a correlation between such factors as inflation, interest rates, etc. and the equity market decline as well as to determine the most decisive factor that may produce the said result. Major findings of this article are as follows: (1) the Lithuanian equity market decline coincides with the increase in the interest rates and the current account deficit; (2) they can be triggered by financial crises in other countries which maintain close trade relations with Lithuania; (3) movements of the Lithuanian equity market can depend on psychological factors.